2022
DOI: 10.1002/acn3.51527
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic profiling of sporadic late‐onset nemaline myopathy

Abstract: Objective To define the proteomic profile of sporadic late‐onset nemaline myopathy (SLONM) and explore its pathogenesis. Methods We performed mass spectrometry on laser‐dissected frozen muscle samples from five patients with SLONM, three of whom with an associated monoclonal protein (MP), and four controls, to determine the proteomic profile of SLONM. Furthermore, we assessed the role of the MP by evaluating the expression of the immunoglobulin light chain variable regions (IGVL). Results There were 294 differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
(87 reference statements)
2
2
0
Order By: Relevance
“…In addition to these, extracellular matrix and nuclear proteins were over-represented in nemaline rod areas in our samples. A similar finding was observed in a recent proteomic analysis comparing rod-containing fibers from 5 SLONM patients to healthy control tissue [ 42 ]. Presence of extracellular matrix proteins accompanying the accumulation of Z-disc-related proteins was also shown by proteomic studies within protein aggregates in myotilinopathy and filaminopathy, two myofibrillar myopathies [ 43 , 44 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In addition to these, extracellular matrix and nuclear proteins were over-represented in nemaline rod areas in our samples. A similar finding was observed in a recent proteomic analysis comparing rod-containing fibers from 5 SLONM patients to healthy control tissue [ 42 ]. Presence of extracellular matrix proteins accompanying the accumulation of Z-disc-related proteins was also shown by proteomic studies within protein aggregates in myotilinopathy and filaminopathy, two myofibrillar myopathies [ 43 , 44 ].…”
Section: Discussionsupporting
confidence: 89%
“…Thus, it also provides further rationale for the use of plasma cell targeting chemotherapy for treatment of SLONM [ 55 ]. While all SLONM specimens showed MHC-I reactivity predominantly involving atrophic fibers, as previously reported [ 42 ], only 5 demonstrated diffuse kappa LC sarcoplasmic staining. Due to extreme heterogeneity of treatment (including intravenous immunoglobulins, methylprednisolone, methotrexate, mycophenolate mofetil, and autologous stem cell transplant) and variable length of follow-up, we were unable to assess whether patients with SLONM who had kappa LC-positive muscle fibers responded better to treatment.…”
Section: Discussionsupporting
confidence: 80%
“…An immune-mediated etiology has been implicated in SLONM [2] [3] [4] [5] [9]. Inflammatory features such as CD68 positive macrophage infiltration, mild MHC expression have been reported without the presence of lymphocytes [2] [4].…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed evidence for upregulation of immune-related proteins despite the lack of inflammation on muscle biopsy in SLONM [9], suggesting that immune-related processes are involved in all cases, but to various extent. MGUS could be a sign for a more aggressive immune response [9].…”
Section: Discussionmentioning
confidence: 99%